2017
DOI: 10.1177/2309499016684322
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of patients with unstable pelvic ring fracture

Abstract: The purpose of this study was to evaluate factors that correlated with unsatisfactory short- and long-term outcome in patients who sustained unstable pelvic ring fracture. The study subjects of this study were those of type B and C pelvic ring fractures (82 patients; mean age 54 years). Age, gender, associated injuries, fracture type, Injury Severity Score rating and treatment methods were assessed, and Majeed score for functional outcome and radiographic studies at 1 year after injury (short-term) and at fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 25 publications
0
31
2
3
Order By: Relevance
“…Seven studies [ 19 , 38 , 39 , 46 , 50 , 51 , 53 ] only described the mean, ranging from 75 up to 95. Three studies [ 20 , 21 , 35 ] combined ‘excellent’ and ‘good’ results to ‘satisfactory’ (range 56–85%) and ‘poor’ and ‘fair’ to ‘unsatisfactory’ (range 15–37%). The Iowa Pelvic Score (IPS) was used by one study [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies [ 19 , 38 , 39 , 46 , 50 , 51 , 53 ] only described the mean, ranging from 75 up to 95. Three studies [ 20 , 21 , 35 ] combined ‘excellent’ and ‘good’ results to ‘satisfactory’ (range 56–85%) and ‘poor’ and ‘fair’ to ‘unsatisfactory’ (range 15–37%). The Iowa Pelvic Score (IPS) was used by one study [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies described physical functioning at different time points, and almost all of them showed improved scores at a later stage. Kokubo et al [ 35 ] applied the MPS at one year and once again after a mean of 7.4 years, while Li et al [ 36 ] also applied the MPS at one year and 10 years after the injury. Kokubo et al found satisfactory (excellent + good) results of 63% after 1 year and 85% after 7.4 years.…”
Section: Resultsmentioning
confidence: 99%
“…Posterior pelvic ring injuries are severe and difficult to diagnose, 7 8 9 10 often requiring urgent stabilization to reestablish the polytraumatized patient from the hemodynamic point of view, 11 12 13 14 and/or subsequent surgical procedures to fix fractures or dislocations, enabling the patient to return to his or her best functional condition.…”
Section: Discussionmentioning
confidence: 99%
“…As lesĂ”es do anel pĂ©lvico posterior sĂŁo graves e de difĂ­cil diagnĂłstico, 7 8 9 10 exigindo, muitas vezes, estabilização de urgĂȘncia que restabeleça, do ponto de vista hemodinĂąmico, o paciente politraumatizado 11 12 13 14 e/ou procedimentos cirĂșrgicos subsequentes com vistas Ă  fixação de fraturas ou luxaçÔes, permitindo o retorno do paciente Ă  sua melhor condição funcional.…”
Section: Discussionunclassified
“…As lesĂ”es pĂ©lvicas podem danificar as estruturas intrapĂ©lvicas e o feixe neurovascular, produzindo hemorragias graves com altas taxas de mortalidade. 1 2 3 4 …”
Section: Introductionunclassified